ANALYSIS OF THE IMPEDIMENTS TO THE EFFECTIVE MANAGEMENT OF MEGA SPORTING EVENTS: A CASE OF THE FIFA 2022 WORLD CUP IN QATAR - Khalifa, Nasser AL-Dosari (European Journal of Business and Strategic Management, 2020)
Purpose: This study sought to analyse the factors that impede the effective management of mega sporting events based on the FIFA 2022 World Cup in Qatar. The specific objectives of the study were: to analyse the factors that impede the effective preparation of the 2022 FIFA World Cup in Qatar; to assess the impact of the prevailing circumstances on the 2022 FIFA event management; and to suggest the best practices that can be adopted in pursuit of ensuring that the 2022 FIFA World Cup (FWC) preparations are on course and the positive impacts are long-lasting. Methodology: The study employed a mixed-method research design consisting of cross-sectional, exploratory, descriptive and causal research designs. Primary data was collected from the respondents using structured questionnaires that were administered online after seeking the consent of the respondents. The study employed a sample size of 90 respondents who were randomly sampled from the three stakeholder bodies that would deliver the 2022 FIFA World Cup, including the Supreme committee, Ministry of Culture and Sports and the Qatar Olympic Committee (QOC). The quantitative data collected was analysed using Microsoft Excel and the SPSS version 25 for data analysis through the use of both descriptive statistics and inferential analyses. The findings of the study were presented using appropriate charts and Tables. Findings: The conclusive findings of this study indicated that sports governance impedes the effective preparation and management of the 2022 FIFA World Cup in Qatar. Unique contribution to theory, practice and policy: To address this, the study recommended that the Supreme Committee (SC) should balance aspects of centralisation with decentralisation in sports management. Further, SC should develop grassroots football by increasing the number of football associations participating in the organisation of the FWC event.